2001
DOI: 10.1002/1096-8628(20010115)98:2<137::aid-ajmg1022>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Distal 13q Deletion Syndrome and the VACTERL Association: Case report, literature review, and possible implications

Abstract: We present a case of a child with del(13) (q31.1qter), VACTERL association, and penoscrotal transposition. Deletion of the distal long arm of chromosome 13 is associated with variable phenotypes. These phenotypes are divided into three clusters; each cluster represents a specific deleted segment of 13q. Individuals with deletions of a critical region at 13q32 have multiple congenital malformations that include components of the VACTERL association. Our patient had all six manifestations of VACTERL association.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
45
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 87 publications
4
45
0
1
Order By: Relevance
“…In accordance with this, previous studies have identified several de novo chromosomal microaberrations, which are likely to be disease causing. [5][6][7][8][9][10][11][12][13][14][15][16] However, none of these de novo chromosomal microaberrations has led to the identification of a disease-causing gene and the etiology in most cases is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with this, previous studies have identified several de novo chromosomal microaberrations, which are likely to be disease causing. [5][6][7][8][9][10][11][12][13][14][15][16] However, none of these de novo chromosomal microaberrations has led to the identification of a disease-causing gene and the etiology in most cases is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Reported environmental factors include maternal diabetes, uterine vascular pathology, and infertility treatment [13][14][15][16]. However, reports of familial occurrence [11], and the presence of chromosomal (micro-) aberrations in affected individuals [17][18][19][20][21][22][23][24] emphasize the importance of possible genetic factors in the etiology of the disorder.…”
Section: Introductionmentioning
confidence: 99%
“…This case highlights the phenotypic overlap of Emanuel syndrome and VACTERL association. Combinations of VACTERL defects have been reported in patients with trisomy 18, the 13q deletion syndrome, 4p deletion syndrome, an interstitial deletion of the long arm of chromosome 6, 9qh+, and mosaicism for a small supernumerary ring chromosome derived from the pericentromeric region of chromosome 12 [4,[9][10][11][12][13][14][15]. In addition, a germline mutation of the PTEN gene (chromosome 10q22-23) has been reported in one patient with VACTERL features [16].…”
Section: Discussionmentioning
confidence: 99%
“…Affecting 1 in 5000 live births, it is considered sporadic and multifactorial with no inheritance pattern identified so far [3]. Several etiologic factors have been proposed, including cytogenetic abnormalities, diabetes, Fanconi anemia, CCG repeat expansion in the fragile X syndrome, and mitochondrial disorders [4,5].…”
mentioning
confidence: 99%